2012
DOI: 10.1017/s0007114512000694
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead level modifies the association between dietary antioxidants and oxidative stress in an urban adult population

Abstract: Oxidative stress may be affected by lead exposure as well as antioxidants, yet little is known about the interaction between dietary antioxidants and blood lead levels (BLL) on oxidative stress level. We investigated the interaction between dietary antioxidants and BLL on oxidative stress level. As part of the Biomarker Monitoring for Environmental Health conducted in Seoul and Incheon, Korea, between April and December 2005, we analysed data from 683 adults (female ¼ 47·4 %, mean age 51·4 (SD 8·4) years) who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Also, the OS biomarkers, 8-hydroxydeoxyguanosine (8-OHdG) and γ-glutamyltransferase (GGT), were positively associated with BLLs in two studies (Lee et al 2006 ;Hong et al 2013 ).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Also, the OS biomarkers, 8-hydroxydeoxyguanosine (8-OHdG) and γ-glutamyltransferase (GGT), were positively associated with BLLs in two studies (Lee et al 2006 ;Hong et al 2013 ).…”
Section: Tablementioning
confidence: 99%
“…This biomarker is an oxidized form of DNA that can be quantifi ed to indicate the extent of DNA damage. Among the three studies that measured 8-OHdG, Hong et al ( 2013 ) analyzed data from Korean adults and found that the level of urinary 8-OHdG was greater in participants with higher BLLs (7.0 ± 1.9 μg/dL) compared to those with lower BLLs (2.5 ± 0.6 μg/dL). In contrast, Malekirad et al ( 2010 ) identifi ed an inverse correlation between 8-OHdG and BLLs in occupationally exposed subjects with increased BLLs (9.6 μg/dL ± 3.3), while Garçon et al ( 2007 ) did not fi nd a signifi cant association in workers with higher BLLs (38.7 μg/ dL ± 9.9).…”
mentioning
confidence: 99%
“…On the other hand, 8-OH-dG is produced by the hydroxylation of the guanosine moiety of a nucleic acid base, and is an established marker of DNA oxidation (Valavanidis et al, 2009). The production of both isoprostane (Holt et al, 2009; Tomey et al, 2007) and 8-OH-dG (Hong et al, 2013; Sram et al, 2012; Engstrom et al, 2010) may be affected by nutrients that modulate the biological pathways for the generation of free radicals or influence the balance between free radicals and antioxidant capacity in the body. We investigated the role of two antioxidants, vitamin C and zinc, for which dietary intake information was available, on the association between BLL and urinary concentrations of isoprostane, and 8-OH-dG in first-grade children.…”
Section: Introductionmentioning
confidence: 99%
“…Among workers but not controls, higher scores of the FV pattern were associated with lower OS. In Korean adults, the intakes of vitamin C and E were negatively associated with 8-OHdG concentrations, but only in those individuals who also had low BLL (Hong et al 2013). Similar patterns of findings were reported for the association between vegetable consumption and 8-OHdG (Hong et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In Korean adults, the intakes of vitamin C and E were negatively associated with 8-OHdG concentrations, but only in those individuals who also had low BLL (Hong et al 2013). Similar patterns of findings were reported for the association between vegetable consumption and 8-OHdG (Hong et al 2013). Finally, antioxidant nutrient intake (vitamin A) and a biomarker of exposure to PAH were independently associated with urinary 8-OHdG concentrations in 3–6 y old Japanese children (Mori et al 2011), although it does not appear that effect modification was tested.…”
Section: Discussionmentioning
confidence: 99%